Financial regulation, interest rate responses, and distributive effects - Christian Loenser; Joost Röttger; Andreas Schabert (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper examines financial regulation and distortionary taxes in a heterogeneous-agents economy with pecuniary externalities induced by a collateral constraint. Limiting the loan-to-value ratio benefits only few unconstrained borrowers and reduces ex-ante social welfare. A Pigouvianstyle symmetric debt tax (that subsidizes savings) raises collateral prices and lowers interest rates, which stimulates borrowing and generates welfare gains for almost all income groups. A Pigouvian-style asset subsidy induces a wealth appreciation, while an asset tax particularly benefits lowwealth borrowers and enhances social welfare. Overall, collateral effects are of minor importance and interest rate rather than asset price responses are decisive for welfare effects.
Keywords: D31; E44; G28; H23; 330; Financial regulation; heterogeneous agents; collateral constraint; pecuniary externalities